Boxers` healthcare and the abolition of the headgear in amateur boxing - Sturla, M. I.; Ricagni, I. G.; Ignozza, C.; Rondoni, F.; Bonetti, A.; Ricciardi, L. (Medicina dello Sport, 2020)
The abolition of the headgear for the amateur boxer has opened a discussion on the acute brain damage of the boxer. The pros and cons the use of the headgear are analyzed and the first AIBA statistical data are presented and discussed, taken from a large number of rounds fought with and without a headgear.